Funkcjonowanie polskich migrantów na brytyjskim rynku pracy - Agnieszka Fihel; Emilia Piętka (University of Warsaw, Centre of Migration Research (CMR), 2007)
– Postaccession migration from Poland into the United Kingdom has been perceived by British experts as the most intensive and rapid inflow of foreigners in the whole postwar period of this country. Also from the Polish perspective emigration to the United Kingdom has been a large, if not the largest, outflow of Polish citizens in recent years. On the basis of comprehensive statistical data, this paper pertains to performance of the Polish migrants at the British labour market. The starting point of the analysis is a very good economic situation in the United Kingdom, due to which since the beginning of the 1990s the employment rate and the number of vacancies have increased. The next analysed issue is the recent migration policy of the United Kingdom that excluded labour market restrictions toward the citizens of the new EU member states. As a result of this decision, the mass inflow from those countries, especially from Poland, took place. In this section the following issues are discussed: the postwar flow from Poland into the United Kingdom, the main characteristics of Polish migrants living in this country, the performance of Polish migrants at the British labour market (including economic sectors of employment, occupations undertaken, the wage level, the seasonality of work). Subsequently, the impact of migration from the new EU member states, especially from Poland, on the British population structure and economy is analysed. Collected statistical data indicate that this impact is positive, but rather marginal: neither increase in unemployment at regional labour markets of the United Kingdom, nor decrease in the wage level, nor obtaining of social benefits under false pretences were observed. However, the inflow of Polish labour migrants did not eliminate the problem of huge number of vacancies in the British economy. Finally, the issue of potential return migration from the United Kingdom to Poland is discussed. This phenomenon, also called remigration, to a great extent depends on individual socio-demographic and occupational characteristics of migrants, migration strategies and future situation at the British and Polish labour markets. The conclusions on the future remigration are based on the previous return migration to Poland since 1989 and the past experiences of the South European countries, where large outflow after the accession into the EU took place.
Keywords: 330; Arbeitsmigranten; Migranten; Polen (Personen); Arbeitsmarktintegration; Rückwanderung; Großbritannien